Daily Physical Activity Is Associated with Subcortical Brain Volume and Cognition in Heart Failure. (19th November 2015) - Alosco, Michael L.; Brickman, Adam M.; Spitznagel, Mary Beth; Sweet, Lawrence H.; Josephson, Richard; Griffith, Erica Y.; Narkhede, Atul; Hughes, Joel; Gunstad, John
Abstract: Cognitive impairment in heart failure (HF) is believed to in part stem from structural brain alterations, including shrinkage of subcortical regions. Fortunately, neurocognitive dysfunction in HF can be mitigated by physical activity (PA), though mechanisms for this phenomenon are unclear. PA is protective against age-related cognitive decline that may involve improved structural integrity to brain regions sensitive to aging (e.g., subcortical structures). Yet, no study has examined the benefits of PA on the brain in HF and we sought to do so and clarify related cognitive implications. Fifty older adults with HF completed a neuropsychological battery and wore an accelerometer for 7 days. All participants underwent brain MRI. This study targeted subcortical brain volume given subcortical alterations are often observed in HF and the sensitivity of PA to subcortical structures in other patient populations. Participants averaged 4348.49 ( SD =2092.08) steps per day and greater daily steps predicted better attention/executive function, episodic memory, and language abilities, p 's<.05. Medical and demographically adjusted regression analyses revealed higher daily steps per day predicted greater subcortical volume, with specific effects for the thalamus and ventral diencephalon, p 's<.05. Greater subcortical volume was associated with better attention/executive function, p <.05. Higher daily PA was associated with increased subcortical brain volume and better cognition in older adults with HF. Longitudinal work is needed to clarify whether daily PA can attenuate brain atrophy in HF to reduce accelerated cognitive decline in this population. ( JINS, 2015, 21, 851–860)